Nilai Filosofi “Lopi Sandeq” Dalam Pengelolaan Penghasilan Nelayan Mandar (The Philosophical Value of “Lopi Sandeq” in Managing Mandar Fishermen’s Income) - Susanti, Sri; Djamhuri, Ali; Purwanti, Lilik (Akutansi Bisnis & Manajemen ( ABM ), 2025)
This research was aimed to reveal the meaning of managing fishermen income based on the philosophical values of lopi sandeq. Phenomenology was the method used, with Mandar fishermen as informants. The results showed that the philosophical values of lopi sandeq also influenced the informants in managing their income. The spiritual values in the philosophy of lopi sandeq were reflected on informants’ qana'ah attitude and their standpoint that the uncertain income and the conditions of famine experienced were interpreted as sustenance and the will of Allah SWT. The value of togetherness in the philosophy of lopi sandeq was manifested in the form of cooperation and mutual trust between the informants and their wives in managing the income and financial transparency through verbal communication. The management of fishermen income was interpreted as a separation between meeting daily needs and personal finances through savings and investment activities. This separation was realized by budgeting expenses and avoiding debt. This management income reflected the value of simplicity in the lopi sandeq philosophy.